Beyond grip strength: selective slowing of grip force release but not initiation dynamics in a go/no-go target force–matching task. - Qadri, Syed; Andrade, Jose Roberto Torres; Culp, Seraphina; Lee, Beatrice; Umucu, Emre; Lum, Peter S.; Geed, Shashwati (Frontiers in Aging Neuroscience, 2026)
Introduction: Precise regulation of grip forces is fundamental for skilled object manipulation and independent navigation of everyday activities throughout the lifespan. Maximal grip strength is a widely used biomarker of aging and frailty, but it provides limited insight into the temporal and inhibitory control mechanisms required for dexterous prehension. Evidence suggests that grip-force release, which requires integration of sensory feedback and inhibition of sustained grip, may be particularly vulnerable to aging. Methods: Thirty‑six right‑handed younger and older adults performed a go/no-go target force–matching task in which they generated and maintained a submaximal grip in response to a go cue and withheld responses to a no-go cue. The paradigm was designed to separately quantify the timing and execution dynamics of grip onset and release within a continuous force‑control task, yielding measures of onset and offset reaction times (RTs), force rise and release durations, and commission errors on no‑go trials. Results: Compared with younger adults, older adults exhibited significantly longer grip‑offset RTs but preserved grip‑onset RTs, indicating selective slowing of release initiation. Grip‑force release duration was also significantly longer in older adults, whereas grip‑force rise times did not differ between groups. Older adults committed more commission errors on no‑go trials; error‑onset RTs were comparable across groups, whereas error force‑release duration was prolonged in older adults. Discussion: These findings indicate that aging selectively slows the initiation and execution of grip release, in a manner consistent with vulnerabilities in inhibitory processes rather than generalized motor slowing. The results extend prior evidence of release‑phase vulnerability in aging by separately quantifying release initiation and execution within a paradigm that also indexes inhibitory control failure, and suggest that grip‑offset dynamics may complement traditional grip‑strength assessments in characterizing age‑related motor decline.